RELATIONSHIP BETWEEN WORK STRESS AND AGGRESSION AMONG EMPLOYEES OF THE RESOURCE GROUP (TRG) - Naseem, Abeer; Ahmed, Mahira (European Scientific Journal, ESJ, 2014)
The present study is aimed to find out the relationship between work stress and aggression among employees of The Resource Group (TRG). A pilot study was conducted on a convenient sample consisting 30 employees from KASB Bank. A sample of 120 employees (60 males; 60 females, Married = 58; Unmarried = 62) was selected for the main study from TRG. The instruments used in the study were The Aggression Questionnaire (AQ) and Professional Life Stress Scale (PLSS). The results revealed that there was a significant relationship between the two variables (r = 0.58) at P<0.01.